Information Security Risk Management Web-Based Final Semester Summative Assessment Application Using ISO 27001:2013 - Pamungkas, Ananda Cipta; Hulu, Wegi Salman; Samihardjo, Rosalin (Journal of Information System and Informatics, 2024)
Education is often understood as more than just teaching, but as the transfer of knowledge, transformation of values, and development of character with all related aspects. Digitalization of the need for information and communication technology is increasing to facilitate access to information systems. This research was conducted at SMAN 12 Bandung with the research objective being a form of evaluation of the implementation of ISO 27001:2013 in clause 4.1. up to 10.2 and Annex A is one of the efforts and efforts to improve the PSAS Website Application ISMS. The method used in this research is to collect data in the form of school documents, identify assets, carry out risk assessments, then carry out risk assessments. The methods used are field observations, interviews, and information processing. The research results show that the Risk Opportunity on the PSAS SMAN 12 Bandung Website Application is around 45%, while the risk severity is estimated at 47%, and the Risk Rating is 49%. In processing field observation data, it was concluded that 80% of Class X, XI, and XII. Meanwhile, the percentage related to the implementation and implementation of ISO/IEC 27001:2013 variable procedures on the PSAS SMAN 12 Bandung web application is 81.43%, which has been implemented and applied well. Meanwhile, the percentage of control implemented in the PSAS web ISMS at SMAN 12 Bandung is 100%. Based on these findings, an analysis was carried out using the PDCA (Plan, Do, Check, Act) method in accordance with ISO 27001:2013 standards and procedures to overcome ISMS problems on the Final Semester Summative Assessment Website Application at SMAN 12 Bandung.